The Role of Parents in Managing Negative Emotions in Early Childhood - Efrideanti, Tabina; Vitaloka, Wulansari; Zaki, Amin (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
Emotional development in early childhood is crucial for children's understanding of themselves and their environment. This study aims to describe parental roles in helping 4ÔÇô6-year-old children recognize and manage negative emotions. Using a qualitative case study design, data were collected through interviews, observation, and documentation, and analyzed thematically. Findings show that parents actively use visual media and physical activities to effectively support children's emotional regulation. The study highlights the importance of parental involvement in fostering emotional skills from an early age.